Relationship Of Duration And Frequency Of Playing Online Games With Emotional Mental Problems In Adolescents - Emi sri wahyuni; Fatmawati; Edison Siringoringo (Comprehensive Health Care, 2022)
The duration of playing online games is the length of time someone plays online games. While the frequency is playing online games, that is the level of frequent use of online game games in a day, even per week. The purpose of the study is to find out the relationship between the duration and frequency of playing online games with emotional and mental problems in adolescents in junior high school 19 bulukumba. Research method this study is a type of descriptive correlation research with a crossectional approach. A sample of 49 respondents from all adolescent populations. While the frequency is playing online games, that is the level of frequent use of online game games in a day, even per week. Based on the results of this test, the value of ρ = 0.006 < α = 0.005. Thus, based on the final results, it can be concluded that "there is a duration relationship with the mental problems of respondents who get the moderate frequency of mental problems (4.1%). Based on the results of the chi-square statistical test analysis, the value of ρ = 0.543 > α = 0.005. Thus, based on the final results it can be concluded that "there is not a strong enough frequency relationship with emotional mental problems in adolescents in the state junior high school of 19 bulukumba". The conclusion and suggestion in this study are that there is a relationship between the duration of playing online games with emotional and mental problems, whereas there is no relationship between the frequency of playing online games with emotional or mental problems in adolescents in Junior High School 19 Bulukumba.